Information-bibliographical service of scientific and technical problem of „Application of protective coatings as well as protective and decorative metal coatings" - Varnienė, Regina (Knygotyra, 1990)
The article is devoted to the analysis of information models dealing with the problem of the application of protective coatings as well as protective and decorative metal coatings. Results of investigations reveal the subject structure of the problem, display the core of scientific and industrial journals, and define bibliographical manuals and databases. Based on the developed models, a structure for a problem-oriented data bank is suggested.